Revision of Taiwanese and Ryukyuan species of Propristocera (Hymenoptera: Bethylidae), with description of a new species - Liao, Hauchuan; Terayama, Mamoru; Eguchi, Katsuyuki (Zootaxa, 2019)
The genus Propristocera Kieffer was very recently revived from the synonymy of the genus Apenesia Westwood, and consists of a total of 25 valid species recorded from the Afrotropical, Oriental and Palaearctic regions. Only two of its species, P. formosimonticola and P. pingtungensis, have been previously recorded from Taiwan. In this study, we examined species of Propristocera collected from Taiwan and the Ryukyus based on external morphology, male genital morphology and molecular phylogenetic analyses, gene markers: nuclear 28SrDNA, mitochondrial COI. In consequence, four species were recognized. Propristocera okinawensis had its record expanded from the Ryukyus to Taiwan, whereas P. kusigematii previously known from the Ryukyus was synonymized under P. pingtungensis, which was known from Taiwan. Furthermore, one new species, Propristocera seediq sp. nov., was discovered in Taiwan and the Ryukyus.